2009
DOI: 10.1017/s1368980009005035
|View full text |Cite
|
Sign up to set email alerts
|

The Italian National Food Consumption Survey INRAN-SCAI 2005–06: main results in terms of food consumption

Abstract: Objective: The current paper aims to present the main results of the Italian National Food Consumption Survey INRAN-SCAI 2005-06. Design: A cross-sectional study was performed. Households were randomly selected after geographical stratification of the national territory. Food consumption was assessed on three consecutive days through individual estimated dietary records. Setting: Italy. Subjects: The final study sample comprised 3323 subjects (1501 males and 1822 females) aged 0?1 to 97?7 years belonging to 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
303
6
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 380 publications
(326 citation statements)
references
References 7 publications
15
303
6
2
Order By: Relevance
“…Daily plant consumption (DPC) and body weight (BW) were estimated based on Leclercq et al (2009). Based on the daily metal intake, it was possible to calculate the health risk index, based on Eq.…”
Section: Contamination Indexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily plant consumption (DPC) and body weight (BW) were estimated based on Leclercq et al (2009). Based on the daily metal intake, it was possible to calculate the health risk index, based on Eq.…”
Section: Contamination Indexesmentioning
confidence: 99%
“…Accordingly, values of daily metal intake were extremely low (ranging 0 to 20 μg kg −1 body weight day −1 , data not shown) and this resulted in limited health risk index values. The health risk index was greatest in radish for Cr, Cu and Pb (Table 2), reaching respectively 0.015, 0.13 and 0.45 in adults (70 kg body weight and 0.22 kg day −1 daily plant consumption, Leclercq et al 2009) and 0.032, 0.270 and 0.951 in children (26 kg body weight and 0.13 kg day −1 daily plant consumption, Leclercq et al 2009) (Table 2). The same index was not affected by the crop species in neither adults (0.026) nor children (0.055) when Ni was considered ( Table 2).…”
Section: Trace Metal Contamination Indexesmentioning
confidence: 99%
“…As an example of a European country, data on mean daily consumption of milk and dairy products from an Italian national survey are shown in Table 2 (Leclercq et al, 2009), whereas calcium and vitamin D intakes resulting from the same survey are reported in Table 3 (Sette et al, 2010). The higher density in calcium in female adults with respect to male adults may be in part attributed to a higher proportion of their diet represented by "milk, milk products, and substitutes" (10% in weight of diet in females vs. 9% in males; Sette et al, 2010).…”
Section: Advantages Of the Calcium In Dairy Productsmentioning
confidence: 99%
“…32 The daily intakes were then calculated given the food contamination and the dietary habits of the Italian population (step 4). 33 In the following, these time-variant intakes are qualified as initial intake. We assumed that the intake is an infusion of the same daily dose over 24 h. Redding et al 13 showed that within a day, the exposure scenario does not impact the results of the PBPK model simulations for PCBs and that a more realistic scenario (i.e., the daily dose divided into three meals) is not necessary.…”
Section: A Dynamic Exposure Model To Calculate Daily Intakesmentioning
confidence: 99%